MODEL PENGENDALIAN KESEHATAN TENAGA KERJA PADA KEGIATAN PENGECORAN LOGAM TRADISIONAL STUDI KASUS DI KAWASAN INDUSTRI BATUR KLATEN- JAWA TENGAH - Latifah Hanum Damanik, Adi Heru Husodo, Totok Gunawan, dan Pramono Hadi (Jurnal Teknosains, 2015)
Research conducted at PT. Bonjor Klaten the distribution of the metal dust in a casting chamber having an effect on the health of the workforce. Diseases caused by exposure to chemicals are dominant in the production process of metal casting in the PT.Bonjor Jaya Klaten is silica and manganese. This substance is thought to impact diseases such as silicosis, which silicosis is pneumoconiosis caused sucked (inhaled) dust silica free (SiO2) and suspected disease caused liveliest chemicals silica, the disease is becoming an important  issue for workers at factories has been running for twenty years. The method used in the study with the path analisys. Based on the results obtained that the activity in the kitchen cupola foundry chemicals produce particles coming from the chimney and output channels cupola kitchen spread the longer the exposure, the disease can affect the lungs and skin. Model of labor control in PT . Bonjor in the form of research findings include: digital simulation on the distribution pattern of the direction and the fall of the particle chemical substances silicon and manganese are dispersed in space foundry, planning SOP activity raw material preparation, filling and operation of the kitchen cupola based hazard in the workplace environment, in an effort metal dust pollution control by using personal protective equipment and supervision of the workplace environment, and the application of legislation  occupational safety and health related licensing and application SMK3 company in PT. Bonjor in efforts to control health workers traditionally casting.